Co-occurrence of dual carbapenemases KPC-2 and OXA-48 with the mobile colistin resistance gene mcr-9.1 in Enterobacter xiangfangensis - Yao, Yancheng; Doijad, Swapnil; Falgenhauer, Jane; Schmiedel, Judith; Imirzalioglu, Can; Chakraborty, Trinad (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial infections with the genus Enterobacter are notoriously difficult to treat and often associated with resistance to penicillin, aminoglycosides, fluoroquinolones, and third-generation cephalosporins. Also, Enterobacter species have emerged as the third most common hosts for carbapenemases worldwide, forcing the use of colistin as a “last-resort” antibiotic for the treatment. Studies on the population structure of the genus Enterobacter repeatedly detect E. xiangfangensis as a common clinical species present worldwide. Here, we report on the characteristics of an extreme drug-resistant E. xiangfangensis isolate va18651 (ST88), obtained from a cervical swab of an expectant mother. The isolate was resistant to almost all the classes of antibiotics tested, including β-lactams (viz., penicillins, carbapenems, cephalosporin, monobactams, and their combinations), quinolone, aminoglycosides, and sulfonamide/dihydrofolate reductase inhibitor, and exhibited heteroresistance towards colistin. Analysis of its complete genome sequence revealed 37 antibiotic resistance genes (ARGs), including mcr-9.1, blaKPC-2, and blaOXA-48, encoded on three of the four different plasmids (cumulative plasmidome size 604,632 bp). An unusually high number of plasmid-based heavy metal resistance gene (HRG) clusters towards silver, arsenate, cadmium, copper, mercury, and tellurite were also detected. Virulence genes (VGs) for the lipopolysaccharide and capsular polysaccharide structures, iron acquisition (iroBCDEN, ent/fep/fes, sitABCD, iut, and fur), and a type VI secretion system, together with motility genes and Type IV pili, were encoded chromosomally. Thus, a unique combination of chromosomally encoded VGs, together with plasmid-encoded ARGs and HRGs, converged to result in an extreme drug-resistant, pathogenic isolate with survival potential in environmental settings. The use of a disinfectant, octenidine, led to its eradication; however, the existence of a highly antibiotic-resistant isolate with significant virulence potential is a matter of concern in public health settings and warrants further surveillance for extreme drug-resistant Enterobacter isolates.